Assortative mating but no evidence of genetic divergence in a species characterized by a trophic polymorphism. (17th January 2016) - Colborne, S. F.; Garner, S. R.; Longstaffe, F. J.; Neff, B. D.
Abstract: Disruptive selection is a process that can result in multiple subgroups within a population, which is referred to as diversification. Foraging‐related diversification has been described in many taxa, but many questions remain about the contribution of such diversification to reproductive isolation and potentially sympatric speciation. Here, we use stable isotope analysis of diet and morphological analysis of body shape to examine phenotypic divergence between littoral and pelagic foraging ecomorphs in a population of pumpkinseed sunfish ( Lepomis gibbosus ). We then examine reproductive isolation between ecomorphs by comparing the isotopic compositions of nesting males to eggs from their nests (a proxy for maternal diet) and use nine microsatellite loci to examine genetic divergence between ecomorphs. Our data support the presence of distinct foraging ecomorphs in this population and indicate that there is significant positive assortative mating based on diet. We did not find evidence of genetic divergence between ecomorphs, however, indicating that isolation is either relatively recent or is not strong enough to result in genetic divergence at the microsatellite loci. Based on our findings, pumpkinseed sunfish represent a system in which to further explore the mechanisms by which natural and sexual selection contribute to diversification, prior to the occurrence of sympatric speciation.